The effect of oxygen-containing anions on luminescent properties of CsI - Shpilinskaya, L.N.; Zaslavsky, B.G.; Kovaleva, L.V.; Vasetsky, S.I.; Kudin, A.M.; Mitichkin, A.I.; Charkina, T.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
It has been found that from the series of oxygen-containing impurities CO₃²⁻, SO₄²⁻, HCO₃–, OH–, IO₃–, NO₃–, NO₂–, CNO–, BO₂– only the bivalent ions stimulate an intensive blue luminescence in CsI crystals at UV- or gamma-excitation. The blue luminescence intensity is higher in CsI(CO₃) than in CsI(SO₄) crystals. The nature of blue luminescence components has been considered and two types of centres have been suggested: the impurity type – CO₃²⁻-Va⁺ (395 nm) and the structural one – Va⁺-Vc⁻ (435 nm). A method of deep purification of the melt from oxygen-containing anions during the growth process has been proposed.